An overview of novelties in endoscopic treatment of the bile ducts - Rogowska-Borettini, Kinga; Malmur, Paweł Arkadiusz; Biaduń-Mućko, Weronika; Romanowska, Aleksandra; Wysieńska, Maria; Jóźwiak, Piotr; Rybak, Adam (Quality in Sport, 2026)
The methods used in the diagnosis and treatment of bile duct diseases - ERCP and EUS - are among the most complex procedures in modern medicine. New technologies make it possible to increase the safety and precision of endoscopic procedures. Technical innovations aim to improve image quality through features such as TXI, RDI, DFI-EUS, and LER. In addition, new tools are being developed for use during endoscopy - Tornus ES and the Hanarostent Z-EUS IT stent.